PATIENT AND DESEASE - Sandro Barni (Journal of Cancer Rehabilitation)
During the “Conference Cured and Chronic: a new Journey in cancer experience” held in Siracusa (Italy) on October 23, 2024, Oncologists, General Practitioners, Epidemiologists, Hematologists, Nurses, and Patients' Advocates came together to discuss the clinical implications of the condition of patients beyond the end of oncological treatment. The discussion was well attended and gathered the views of international speakers as well and covered the now inescapable need for characterization of patients who have fnished cancer treatments and are chronic or cured, the need for a new vision of territorial medicine that can also include tertiary prevention, and fnally a new vision of both logistics and methodology of follow-up. The purpose of this work is to get people past the discussion stage and start proposing concrete models that will lead to real improvements in the lives of chronic or cured patients.